2015
DOI: 10.1001/jama.2015.8361
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Stress Reduction for Posttraumatic Stress Disorder Among Veterans

Abstract: IMPORTANCE Mindfulness-based interventions may be acceptable to veterans who have poor adherence to existing evidence-based treatments for posttraumatic stress disorder (PTSD). OBJECTIVE To compare mindfulness-based stress reduction with present-centered group therapy for treatment of PTSD. DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial of 116 veterans with PTSD recruited at the Minneapolis Veterans Affairs Medical Center from March 2012 to December 2013. Outcomes were assessed before, during, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
230
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(242 citation statements)
references
References 35 publications
8
230
1
1
Order By: Relevance
“…[129][130][131][132][133][134][135][136][137][138][139] In a recent pilot study Cole and colleagues 129 investigated standard MBSR as a treatment for both PTSD symptoms and attention difficulties among veterans with PTSD and a history of mild traumatic brain injury (mTBI), reporting low drop-out rates (10%), significant reductions in self-reported PTSD symptoms and significant improvements on attention measures posttreatment. In that study, PTSD symptom reduction was maintained at 3-month follow-up, although attention improvements were not.…”
Section: Mindfulness-based Stress Reduction For Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…[129][130][131][132][133][134][135][136][137][138][139] In a recent pilot study Cole and colleagues 129 investigated standard MBSR as a treatment for both PTSD symptoms and attention difficulties among veterans with PTSD and a history of mild traumatic brain injury (mTBI), reporting low drop-out rates (10%), significant reductions in self-reported PTSD symptoms and significant improvements on attention measures posttreatment. In that study, PTSD symptom reduction was maintained at 3-month follow-up, although attention improvements were not.…”
Section: Mindfulness-based Stress Reduction For Ptsdmentioning
confidence: 99%
“…131,132,134 A handful of RCTs investigating the efficacy of MBSR have been completed among trauma-exposed populations. 133,[136][137][138] The largest of these was a recent study in which 116 veterans with full or subthreshold PTSD were randomly assigned to receive MBSR (augmented to include psychoeducation about trauma) or present-centred therapy (PCT; focused on current problems as manifestations of PTSD). 138 Significantly greater reductions in self-report and clinician-rated (Clinician Administered PTSD Scale [CAPS] 140 ) PTSD symptoms and improvements in quality of life were noted in the MBSR group (medium effect sizes) with adequate retention rates (78%).…”
Section: Mindfulness-based Stress Reduction For Ptsdmentioning
confidence: 99%
“…There is growing evidence suggesting that in addition to cognitive enhancement, engaging in MT programs improves psychological health and reduces symptoms across a variety of disorders (e.g., Gotink et al 2015;Goyal et al 2014), including PTSD (Polusny et al 2015). The field of military medicine has recently recommended MT's use as adjunctive care for servicemembers and veterans suffering from insomnia, PTSD, and chronic pain (Khusid 2013;Khusid andVythilingam 2016a, Khusid andVythilingam 2016b).…”
mentioning
confidence: 99%
“…Neuroimaging studies have shown that PTSD causes lasting changes to the neural circuitry of stress where hypoactive hippocampus and challenged ventromedial prefrontal cortex fail to manage hyperactive amygdala, thereby creating a dysfunctional loop [4][5][6][7]. Studies have also reported that individuals with PTSD experience heightened sympathetic nervous system activity that was absent before the trauma which manifests symptoms of hyperarousal or hypervigilance, poor concentration, anhedonia, elective hypoamnesia, and dysfunctional mood regulation [8,9]. They also tend to experience repetitive flashbacks or upsetting memories, intrusive thoughts, and behavioural avoidance, which may be attributed to the prefrontal cortex failing to regulate the fear response [10].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies using mindfulness with individuals suffering from PTSD have consistently shown that mindfulness not only helps alleviate intrusive thoughts, repetitive flashbacks, behavioural avoidance, hyperarousal, and dysfunctional mood, but also improves concentration and attention, cognitive appraisal, emotional regulation, and re-adjustment to normal life, family, and work [e.g., Copyright: ©2017 Roychowdhury 8,9,[26][27][28][29]. Neuroimaging studies have shown that mindfulness causes increased activity in prefrontal cortex and decreased activity in amygdala, thereby suggesting a mediating functional relationship between the two [30][31][32].…”
Section: Introductionmentioning
confidence: 99%